2020
DOI: 10.1029/2020gl089723
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Inconsistencies in Extreme Precipitation‐Temperature Sensitivities

Abstract: Extreme precipitation events are intensifying with increasing temperatures. However, observed extreme precipitation-temperature sensitivities have been found to vary significantly across the globe. Here we show that negative sensitivities found in previous studies are the result of limited consideration of within-day temperature variations due to precipitation. We find that short-duration extreme precipitation can be better described by subdaily atmospheric conditions before the start of storm events, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…Zhang et al, 2017), statistical methods and inappropriate modeling assumptions (Pumo et al, 2019;Wasko et al, 2015) and mixing of different rainfall types (P. Molnar et al, 2015). The intermittent nature of precipitation can also be responsible for the deviation in scaling (Schleiss, 2018) and Visser et al (2020) argued that this could be resolved by using dry-bulb temperature prior to the storm. Moreover, the localized effects of large-scale circulation patterns enhanced local moisture availability through upward motions and moisture convergence, and local-scale dynamics can influence scaling rates Guerreiro et al, 2018;Magan et al, 2020;Mishra et al, 2012;Pfahl et al, 2017).…”
mentioning
confidence: 99%
“…Zhang et al, 2017), statistical methods and inappropriate modeling assumptions (Pumo et al, 2019;Wasko et al, 2015) and mixing of different rainfall types (P. Molnar et al, 2015). The intermittent nature of precipitation can also be responsible for the deviation in scaling (Schleiss, 2018) and Visser et al (2020) argued that this could be resolved by using dry-bulb temperature prior to the storm. Moreover, the localized effects of large-scale circulation patterns enhanced local moisture availability through upward motions and moisture convergence, and local-scale dynamics can influence scaling rates Guerreiro et al, 2018;Magan et al, 2020;Mishra et al, 2012;Pfahl et al, 2017).…”
mentioning
confidence: 99%
“…Limited moisture availability at higher temperatures was also observed by Molnar et al (2015) in Switzerland, Park and Min (2017) in South Korea, and Peleg et al (2018) in the eastern Mediterranean. Finally, it should be mentioned that, contrary to previous studies, Visser et al (2020) argued that dry-bulb temperature can adequately describe short-duration extreme precipitation if sub-daily atmospheric conditions before the storm events are taken into consideration.…”
Section: 1029/2021jd034972mentioning
confidence: 67%
“…Finally, it should be mentioned that, contrary to previous studies, Visser et al. (2020) argued that dry‐bulb temperature can adequately describe short‐duration extreme precipitation if sub‐daily atmospheric conditions before the storm events are taken into consideration.…”
Section: Introductionmentioning
confidence: 76%
“…Higher moisture availability in the atmosphere with warming has been extensively studied and partially explains the observed and simulated rise in short‐duration precipitation extremes, with stronger updrafts also potentially contributing (Giorgi et al., 2016; Held & Soden, 2006; O’Gorman & Schneider, 2009). Many studies have reported increases in precipitation extremes with temperature following the Clausius‐Clapeyron (CC) rate of 7% per K (Ali et al., 2021; Visser et al., 2020). However, higher scaling rates (so called ‘super‐CC scaling’) have been found for hourly precipitation extremes (Ban et al., 2015; Berg et al., 2013; Drobinski et al., 2018; Hodnebrog et al., 2019; Lenderink & van Meijgaard, 2008; van de Vyver et al., 2019).…”
Section: Introductionmentioning
confidence: 99%